Methods Of Modification of Silicon Acid (Texas Journal of Multidisciplinary Studies, 2022)
Modified silicon acids are produced by combining gels and silicates with thermoplastic material such as wax or polyethylene. Silicone acids can be absorbed either after the formation of silicagels or silicates or by adding aqueous suspension or dispersion of wax thermoplastic material to the silicon acid gels or silicates. It is then mixed and filtered, washed, dried and crushed into pieces. Organically modified silicon acids, gels and silicates are used as dust cleansers in lacquer systems.